E-cigarette use among adolescents in Latin America: A systematic review of prevalence and associated factors - Juan S. Izquierdo-Condoy; Kenny Ruiz Sosa; Camila Salazar-Santoliva; Natalia Restrepo; Guillermo Olaya-Villareal; Juan S. Castillo-Concha; Valentina Loaiza-Guevara; Esteban Ortiz-Prado (Preventive Medicine Reports)
Background: Electronic cigarettes, introduced as a safer tobacco alternative, have unintentionally exposed millions of youths to nicotine and harmful chemicals. Adolescence, a key period for forming lifelong habits, has seen rising e-cigarette use, particularly in developing regions like Latin America, warranting thorough investigation. Objective: To describe the prevalence and factors associated with e-cigarette use among adolescents in Latin America. Methods: A systematic review was conducted according to PRISMA guidelines, covering studies published between 2003 and May 2024. Database searches included PubMed/Medline, Web of Science, Scopus, Google Scholar, Scielo, and LILACS. A total of 582 studies were identified, of which 14 met the inclusion criteria. Study data were synthesized and assessed using the Newcastle-Ottawa Scale and Joanna Briggs Institute checklist. Results: The prevalence of e-cigarette among adolescents in six Latin American countries ranged from 2.6 % to 64.2 %, with a pooled mean prevalence of 18.9 %, and lifetime use higher than current use. Key associated factors included male sex, concurrent use of tobacco and other substances, social influences, and exposure to online advertising. A widespread lack of knowledge regarding e-cigarette risks, coupled with limited regulatory oversight, may be contributing to higher usage rates. Conclusion: This review underscores critical gaps in data on adolescent e-cigarette use in Latin America and highlights the need for expanded research and targeted public health interventions. Nearly one-fifth of adolescents reported using e-cigarettes. Comprehensive prevention programs addressing factors associated with adolescent e-cigarette use in Latin America, involving diverse stakeholders and integrating education, school-based policies, social media campaigns, and policy restrictions, are strongly recommended.